Temporal trends of risk profile among patients admitted with acute coronary syndrome - Abreu, G (2015)
Background: Clinical practice focuses on the primary prevention of cardiovascular (CVD) disease through the modification and pharmacological treatment of elevated risk factors, in order to minimize long-term CVD risk. Aim: To determine if there are differences in risk profile of patients admitted with acute coronary syndrome over time. Methods: We analysed 4871 patients admitted consecutively in our coronary care unit with a diagnosis of ACS and included in a prospective registry, from January 2002 to October 2013. Patients were divided in 3 groups of 4 consecutive years: group 1 – from 2002 to 2005 (n=1245, 25.6%); group 2 – from 2006 to 2009 (n=1562, 32%); group 3 - from 2010 to 2013 (n=2064, 42.4%). For each group we studied the prevalence of conventional risk factors (CRF) including diabetes, hypertension, smoking and dyslipidaemia over time and compared findings according to sex and type of acute coronary syndrome: Results: Women were less prevalent in group 3 (26.2% vs 26.9% vs 22.6%, p=0.006). Temporal trends of age and diabetes didn’t show statistic signify. Group 2 and 3 evidenced higher body mass index (26.48±4.0 vs 27.13±5.8 vs 27.15±4.67 kg/m2; p<0.001), had higher prevalence of dyslipidaemia (43.1% vs 49.2% vs 56.3%; p<0.001), smoking (39.4% vs 65.0% vs 64.4%; p<0.001) and hypertension (55.7% vs 65.0% vs 64.4%; p<0.001). We found at least 1 CRF in 92,4% of patients. The first temporal period had higher prevalence of 1 or 2 CRF, on the contrary two thirds of patients in group 3 had 2 or 3 CRF. Over time, hypertension was more prevalent in women (69.3% vs 77,4% vs 78.6%; p=0,007), on the other hand, smoking and dyslipidaemia occurred more often in men. It was observed an increasing tendency of smoking (44% vs 41.6% vs 54%; p<0.001) and dyslipidemia (37.2% vs 45.3% vs 50.5%, p<0.001) over time. In those patients admitted with STEMI, it was observed an increased tendency on smoking. The last period registered LDL levels >100 mg/dl more often (66% vs 57% vs 68.8%; p=0.022), but higher control of systolic blood pressure below 140mmHg (54.2% vs 59.6% vs 65.7%, p<0.001. Conclusion: We found that the risk profile of patients presenting with acute coronary syndrome worsened over the years. In recent time, patients had more CRF, being smoking and hypertension the leaders.